1974
DOI: 10.1097/00000658-197406000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Gastrin Release by Ethanol in Man and in Dogs

Abstract: In man, oral or intravenous administration of ethanol caused a small but definite increase in peripheral serum gastrin concentration (measured by radioimmunoassay). In dogs, perfusion of the antrum with 10% ethanol caused an immediate increase in gastrin levels in the antral venous outflow. Acidification of the perfusate did not totally block the gastrin release from the antrum. Intravenous infusion of ethanol in dogs caused release of gastrin from the antrum.IN 1898, CHrTlENDEN AND cowoRERs3 reported that ing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
17
0
2

Year Published

1974
1974
2003
2003

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 9 publications
4
17
0
2
Order By: Relevance
“…The small, but significant, elevation in the plasma concentration of gastrin early after oral intake of alcohol is in line with the results reported by Hajnal et al 15 and Becker et al, 17 who suggested that the enhancement of gastric secretion caused by the intake of alcohol is partially mediated by gastrin. With regard to CCK, enhancement of CCK secretion by alcohol intake has been reported in rats.…”
Section: Discussionsupporting
confidence: 90%
“…The small, but significant, elevation in the plasma concentration of gastrin early after oral intake of alcohol is in line with the results reported by Hajnal et al 15 and Becker et al, 17 who suggested that the enhancement of gastric secretion caused by the intake of alcohol is partially mediated by gastrin. With regard to CCK, enhancement of CCK secretion by alcohol intake has been reported in rats.…”
Section: Discussionsupporting
confidence: 90%
“…Ethanol has been shown to release gastrin both in man and dogs [2], The current study with rats not only confirms these findings but also reveals for the first time that the blood level of somatostatin is increased after ethanol administration. However, the mechanism for either effect has not been examined.…”
Section: Discussionsupporting
confidence: 84%
“…The possibility of ethanol directly stimulating (due to its hy pertonicity and higher pH) the chemoreceptors in the gastrointestinal tract [3,7,10], to account for the release of both gastrin and somatostatin, should be considered. How ever, since intravenous infusion of ethanol can also increase gastrin blood levels [2], this suggests that ethanol may release gastrin and somatostatin by local as well as systemic actions on the gut.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is more likely that ethanol acts directly on gastric mucosa by local irritation (Code, 1953). Becker et al (1974) reported a small and transient increase in gastrin release after intravenous administration of 7 % ethanol. In contrast to our findings the authors observed a significant increase in gastrin secretion following oral ingestion of 18 and 50 % ethanol in man.…”
Section: Discussionmentioning
confidence: 99%